The Ecranisation of KKN di Desa Penari Novel by Simpleman to Film by Awi Suryadi - Nisak, Lukluun; Chamalah, Evi; Turahmat, Turahmat (Universitas Muria Kudus, 2023)
Tujuan penelitian ini adalah (1) menganalisis proses ekranisasi yang muncul pada alur dalam novel dan film KKN di Desa Penari, (2) menganalisis proses ekranisasi yang muncul pada tokoh dalam novel dan film KKN di Desa Penari, dan (3) menganalisis proses ekranisasi yang muncul pada latar dalam novel dan film KKN di Desa Penari. Data dikumpulkan dengan metode kualitatif deskriptif. Data dalam penelitian ini adalah novel dan film. Adapun sumber data dalam penelitian ini adalah novel KKN di Desa Penari karya SimpleMan dan film KKN di Desa Penari karya sutradara Awi Suryadi. Proses pengumpulan data dilakukan dengan menggunakan tiga tahapan, yakni teknik membaca, menonton, dan mencatat. Setelah itu, analisis data dilakukan dengan melakukan pembacaan pada novel, membedah novel, mengamati film, membedah film, membandingkan novel dan film, mengamati gejala transformasi, dan menganalisa transformasi. The aims of this study were (1) to analyze the ecranization process that appears in the plot of the KKN novel and film in the Penari Village, (2) to analyze the ecranization process that appears in the characters in the KKN novel and film in the Penari Village. Penari Village, and (3) analyze the ecranization process that appears in the setting of the KKN novel and film in the Penari Village. Data was collected with a qualitative descriptive method. The data in this study are novels and films. The data sources in this study are the KKN novel in the Dancer Village by SimpleMan and the KKN film in the Penari Village by director Awi Suryadi. The data collection process was carried out using three stages, namely reading, observing, and note-taking techniques. After that, data analysis was carried out by reading novels, dissecting novels, observing films, dissecting films, comparing novels and films, observing transformation phenomena, and analyzing transformations. The results obtained from this study are, (1) the category of plot shrinkage aspect consists of 20 description sections, for the aspect of adding plots there are 13 scenes, and for the aspect of variation category changes there are 11 variations. (2) there are 7 characters in the shrinking aspect category and for the varied change category there are 4 characters, while the addition aspect is not found. (3) there are 14 backgrounds for the reduced aspect categories, three backgrounds for changed aspects, while additional aspects are not found.